Specific Patterns of Cdc42 Activity Are Related to Distinct Elements of T Cell Polarization - Tskvitaria-Fuller, Irina (2006)
T cell polarization toward and within the cellular interface with an APC is critical for effective T cell activation. The Rho family GTPase Cdc42 is a central regulator of cellular polarization. Using live-cell imaging, we characterized the spatiotemporal patterns of Cdc42 activity and their physiological regulation. Using three independent means of experimental manipulation of Cdc42 activity, we established that Cdc42 is a critical regulator of T cell actin dynamics, TCR clustering, and cell cycle entry. Using quantification of three-dimensional data, we could relate distinct spatiotemporal patterns of Cdc42 activity to specific elements of T cell activation. This result suggests that Cdc42 activity in specific locations at specific times is most critical for its function in T cell activation.